Galloping of two-dimensional section of a marine riser attached with fairing under different inflow angles. (15th September 2022) - Xia, Xiang; Zeng, Haiyan; Wang, Zhengwei; Zhou, Lingjiu; Liu, Chengming
Abstract: Fairing is one of the most effective and popular devices for suppressing vortex-induced vibration (VIV) of marine risers. However, when the fairing is stuck and cannot rotate due to biological contamination and other reasons, it may cause serious galloping oscillation and endanger the safety of the riser. In this paper, a reliable two-dimensional fluid-structure interaction (FSI) model with two degrees of freedom (DOF) was established based on computational fluid dynamics (CFD) and finite element method (FEM). The steady flow fields and galloping characteristics of a faired riser under different inflow attack angles were studied by numerical method. The results showed that when the structure is stationary, there is a critical attack angle α c  ∈ (25°, 30°), which divides the vortex shedding state and the variation law of the hydrodynamic coefficient. This is because when the inflow attack angle α  >  α c, a reattachment of the shear layer occurs on one side of the fairing. In the 2 DOF FSI analysis, typical cross-flow (CF) direction galloping was observed in the region of α  <  α c . When α  >  α c, the oscillation was relatively weak, and the amplitudes in the in-line (IL) and CF directions were similar. When the α was near α c, the vibration was smallest. According to the structure of the wake vortex, the stable reattachment of the separated shear layer generated on one side of the fairing affected by the inflow attack angle is not easy to cause galloping. Only when the periodic reattachment occurs, it will trigger a strong galloping. Highlights: There is a critical attack angle α c to separate the flow performance around a static fairing. The response characteristics of the vibrating fairing on the two sides of α c are very different. The trajectory of the fairing changes regularly with the attack angle and the reduced velocity. Periodic rather than stable "reattachment" prone to fairing galloping.